Appreciating Software Engineering as a Character in the Ethics/Moral Paradigm (International Journal of Innovative Research in Computer Science & Technology, 2020)
Gone are the days when “Might is Right”,  the law of Jungle use to prevail everywhere, though it still  exists but to a much lesser degree. This means that the  people & nations have understood their duties & right  towards others in the current information or precisely the  media age. This would not have come to the existence in  the absence of the revolutionary nature of the computer  evolution (encompassing almost all the disciplines of life)  either Relativism or Emotivism paradigm. In my opinion  Ethics is” Acknowledgement of others rights (whosoever &  whatsoever) is directly or indirectly related to you &  discharging your duties and responsibilities to them to the  utmost satisfaction of your inner self. ” This research  based on the lifelong (twenty eight years ) teaching the  software Engineering as a computer discipline has  envisioned the researcher to attribute software Engineering  as a character in the light of the various ethical and moral  considerations , theory and Practices.
Keywords: Knowledge; Data; Ethics; Emotivism; Character; S. E; Practices